2019
DOI: 10.1002/ardp.201900002
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of 1,2,4‐triazolo[1,5‐a]pyrimidine derivatives as PDE 4B inhibitors endowed with bronchodilator activity

Abstract: A series of 1,2,4‐triazolo[1,5‐a]pyrimidine derivatives was designed, synthesized, and screened for their phosphodiesterase (PDE 4B) inhibitory activity and bronchodilation ability. Compound 7e showed 41.80% PDE 4B inhibition at 10 µM. Eight compounds were screened for their bronchodilator activity, where compounds 7f and 7e elicited promising bronchodilator activity with EC50 values of 18.6 and 57.1 µM, respectively, compared to theophylline (EC50 = 425 µM). Molecular docking at the PDE 4B active site reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Substitued 7‐oxo‐4,7‐dihydro‐[1,2,4]‐triazolo[1,5‐ a ]pyrimidine‐6‐carbohydrazide 48 (88–95 %) were synthesised in two steps (Scheme 28) involving diethyl ethoxymethylene malonate and substitued 1,2,4‐triazol‐5‐amine in acetic acid in the first step followed by the reaction of selected esters with hydrazine hydrate in methanol gave the corresponding hydrazides compounds [38] …”
Section: Triazolopyrimidine Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Substitued 7‐oxo‐4,7‐dihydro‐[1,2,4]‐triazolo[1,5‐ a ]pyrimidine‐6‐carbohydrazide 48 (88–95 %) were synthesised in two steps (Scheme 28) involving diethyl ethoxymethylene malonate and substitued 1,2,4‐triazol‐5‐amine in acetic acid in the first step followed by the reaction of selected esters with hydrazine hydrate in methanol gave the corresponding hydrazides compounds [38] …”
Section: Triazolopyrimidine Synthesismentioning
confidence: 99%
“…Substitued 7-oxo-4,7-dihydro-[1,2,4]-triazolo[1,5-a]pyrimidine-6-carbohydrazide 48 (88-95 %) were synthesised in two steps (Scheme 28) involving diethyl ethoxymethylene malonate and substitued 1,2,4-triazol-5-amine in acetic acid in the first step followed by the reaction of selected esters with hydrazine hydrate in methanol gave the corresponding hydrazides compounds. [38] In other scientific work, Abd El-Aleam et al [39] designed and synthesized a series of [1,2,4] ChemistrySelect synthesized compounds. The last two steps take place with lower yields probably due to the difficulty of isolating and purifying the respective compounds formed (52 and 53).…”
Section: Synthesis Of Triazolopyrimidines Derivatives From Aminotriazolementioning
confidence: 99%
“…reported the bronchodilator activity of a set of 1,2,4-triazolo[1,5- a ]pyrimidine derivatives 272 ( Fig. 48 ) as phosphodiesterase 4B inhibitors [ 244 ]. The study revealed that compounds 272a and 272b with EC 50 values of 18.6 and 57.1 μM, respectively, showed better bronchodilator activity than the reference theophylline (EC 50 : 425 μM).…”
Section: Miscellaneousmentioning
confidence: 99%
“…These azolo[1,5- a ]-pyrimidines have been found to exhibit antiviral, anti-inflammatory, antibacterial, antifungal, antiparasitic, antitumor, and other biological activities. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to the SciFinder database, more than 1000 original papers and patents have been published over the last 5 years (2015–2019), thus indicating great interest in this class of compounds. These azolo­[1,5- a ]-pyrimidines have been found to exhibit antiviral, anti-inflammatory, antibacterial, antifungal, antiparasitic, antitumor, and other biological activities …”
Section: Introductionmentioning
confidence: 99%